1998
DOI: 10.1161/01.atv.18.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Supplementation Reduces Blood Homocysteine Levels

Abstract: Abstract-Hyperhomocysteinemia is a risk factor for atherosclerosis and thrombosis and is inversely related to plasma folate and vitamin B12 levels. We assessed the effects of vitamin supplementation on plasma homocysteine levels in 89 patients with a history of recurrent venous thrombosis and 227 healthy volunteers. Patients and hyperhomocysteinemic (homocysteine level Ͼ16 mol/L) volunteers were randomized to placebo or high-dose multivitamin supplements containing 5 mg folic acid, 0.4 mg hydroxycobalamin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(41 citation statements)
references
References 31 publications
4
34
1
2
Order By: Relevance
“…In one study, healthy subjects were given a multivitamin supplement containing 0.4 mg/day of hydroxicobalamin, 5 mg of folic acid, and 50 mg of pyridoxine (den Heijer et al, 1998); the results demonstrated a 49% reduction in the basal median value of Hcy, among individuals with the 677TT genotype. In another study, a similar response could only be detected among subjects with hyperhomocysteinemia, who were carriers of the polymorphism 677C4T, who had taken the supplements over 4 weeks, and these had either normal or elevated levels of vitamin B 12 (D'Angelo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, healthy subjects were given a multivitamin supplement containing 0.4 mg/day of hydroxicobalamin, 5 mg of folic acid, and 50 mg of pyridoxine (den Heijer et al, 1998); the results demonstrated a 49% reduction in the basal median value of Hcy, among individuals with the 677TT genotype. In another study, a similar response could only be detected among subjects with hyperhomocysteinemia, who were carriers of the polymorphism 677C4T, who had taken the supplements over 4 weeks, and these had either normal or elevated levels of vitamin B 12 (D'Angelo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Developing recommendations combining folic acid supplementation with other B vitamins, particularly B 12 may be preferable. Available evidence indicates that combined supplementation enhances the reduction of hyperhomocysteinemia in individuals with a deficiency of both vitamins (den Heijer et al, 1998), and probably reduces the risk of spontaneous abortion among MTHFR 677TT and transcobalamin 776GG carriers (Zetterberg et al, 2003). However, more important is the fact that folic acid supplementation alone is likely to mask a deficiency in vitamin B 12 (Obeid et al, 2002) and consequently hampers the possibility of correcting the levels of Hcy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent intervention studies have shown that a similar reduction in plasma tHcy can be accomplished by far smaller supplements, 500 mg (den Heijer et al, 1998;Brouwer et al, 1999a, b). We found that in regular users of > 300 mg supplementary folic acid per day (mean 513 mg) the mean plasma tHcy concentration was 28% lower compared to non-users.…”
Section: Discussionmentioning
confidence: 99%
“…To date, folic acid doses of 5 to 10 mg per day are currently used. Nevertheless, some data now suggest that a daily administration of folic acid at a dose lower than 1 mg may be adequate to reverse hyperhomocysteinemia (Boushey et al, 1995;Brattström et al, 1998;den Heijer et al, 1998;Rimm et al, 1998). In a recent study, cereal fortification, providing 499 and 665 g of folic acid daily, increased plasma folic acid by 64.8% and 105.7%, respectively, and decreased plasma homocysteine by 11% and 14%, respectively .…”
Section: Vitamin Treatment Of Hyperhomocysteinemiamentioning
confidence: 99%